Differences Between Internal And External Audits In Detecting Fraud: The Moderating Role Of Professional Skepticism As A Moderating Variabel - Anandita, Rissa; Zakaria, Fakhmi; Adhi Prasetyo, Rifki (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This research aims to examine the differences between internal and external audit in detecting fraud, as well as the role of professional skepticism as a moderating variable between independence and audit experience in fraud detection. The population and research object are internal and external auditors in Central Java Province. The sampling technique used in the research was purposive sampling, obtaining a sample of 155 internal auditors and 177 external auditors. The research method uses Structural Equation Model (SEM) with the help of Smart-PLS 4 software. Data was obtained using a questionnaire. The research results were divided into two groups, namely in the internal and external auditor groups, where there were similar results which stated that professional independence and auditor experience had a positive impact on fraud detection. The moderating variable professional skepticism is unable to moderate the relationship between professional independence and auditor experience in detecting external and internal auditor fraud. However, in the professional internal auditor group, skepticism was able to moderate the relationship between auditor experience and fraud detection.